Estimation of flood hazard area in Temerloh, Pahang Malaysia by using Geographic Infomation System approach / Muhammad Kashfi and Muhammad Adam Irfan Sabarudin - Kashfi, Muhammad; Sabarudin, Muhammad Adam Irfan (Universiti Teknologi MARA (UiTM), 2024)
Floods are a continuous problem in Malaysia, particularly in Temerloh, Pahang, where yearly monsoon rains often cause considerable flooding throughout the region. The primary goal of this project is to create a detailed flood hazard map using ArcGIS Pro and a variety of spatial analytic tools to appropriately analyze flood risk in the Temerloh district. The project combines secondary data from trustworthy sources such as the USGS, My Met Malaysia, and NASA Power, which is complemented by custom-created shapefiles adapted to certain geographical features.